A foreign devil in China : the story of Dr. L. Nelson Bell - Pollock, John (Minneapolis, Minn. World Wide Publications, 1988)
Presents the life of Dr. Nelson Bell, a missionary in China.
Keywords: Bell, L. Nelson -- (Lemuel Nelson), -- 1894-1973. Bell, L. Nelson -- (Lemuel Nelson), -- 1894-1973 Religious Missions -- history -- China